Prevalence and Risk Factors for Antenatal Depression in Ethiopia: Systematic Review. (9th July 2018) - Getinet, Wondale; Amare, Tadele; Boru, Berhanu; Shumet, Shegaye; Worku, Wubet; Azale, Telake
Abstract : Introduction . Antenatal depression is a syndrome, in which women experience depressed mood, excessive anxiety, insomnia, and change in weight during the period of pregnancy. Maternal depression negatively influences child outcomes and maternal health. Antenatal depression was measured by different rating scales, namely, BDI, EPDS, and PHQ. The objective of this systematic review was to synthesize logical evidence about the prevalence and potential risk factors of antenatal depression in Ethiopia. Methods . Our team explored multiple databases including PSYCHINFO, MEDLINE, Embase, Google Scholar, and Google Search to detect studies published with data on the prevalence of antenatal depression. We found 246 research papers on antenatal depression, of which 210 did not correspond to the title and 27 were duplicates. Subsequently, nine articles were used for synthesis prevalence, of which four studies were selected in the analysis of the effect of unplanned pregnancy on antenatal depression. Figures were extracted from published reports and grey literature, and any lost information was requested from investigators. Estimates were pooled using random-effects meta-analyses. Results . The pooled prevalence of antenatal depression for five studies selected, which had used BDI, was 25.33 (20.74, 29.92). The other four studies that had included other screening tools (3 EPDS and 1 PHQ) had the prevalence decreased to 23.56 (19.04, 28.07), and the pooled effect of unplanned pregnancy on antenatal depression was 1.93 (1.81, 2.06). Factors such as age, marital status, income, occupation, history of the previous mental disorder, antenatal follow-up, unplanned pregnancy, complication during to pregnancy, age of mother during pregnancy, conflict, and social support were associated with antenatal depression. Conclusions . Antenatal depression is a common maternal problem; further attention should be given to the effect of unplanned pregnancy, social support, pregnancy-related complications, family conflicts, and violence on pregnant women. All these are possible risk factors for antenatal depression.